Genomic prediction of cardiovascular events in a coronary Southern European population. (14th October 2021) - Mendonca, F; Mendonca, M I; Santos, M; Temtem, M; Sousa, J A; Sousa, A C; Henriques, E; Freitas, S; Rodrigues, M; Borges, S; Guerra, G; Drumond, A; et al.
Abstract: Background: Traditional and clinical risk factors are indicators of atherosclerosis over time and strong independent predictors of cardiovascular events, but it is unknown whether other genetic markers could provide information about the evolution of atherosclerotic coronary artery disease (CAD). Objective: We propose identifying the genetic predisposition to atherosclerotic plaque progression and events occurrence, through a study cohort from GENEMACOR study population. Methods: We performed a study with a cohort of 1, 712 patients who underwent coronary angiography with more than 70% stenosis of at least one main coronary vessel, during a mean follow-up of 5 years (amplitude range 20 years). 33 SNPs associated with risk of CAD in previous GWAS, were genotyped by TaqMan assays methodology. The best model in the bivariate analysis at 95% CI with all genetic variants was generated, to investigate their association with prognostic and events occurrence. The hazard function at a set of confounding-variables was determined to evaluate their relationship with the event's incidence by the Cox survival analysis regression model. Finally, we constructed Kaplan–Meier cumulative-event curves for the significant variants. Results: The analysis revealed two SNPs associated with the progression of atherosclerosis and events occurrence: rs12190287 G>C in the TCF21 gene on chromosome 10 (dominant model; OR=1.542; 95% CI 1.069 – 2.224; p=0.020) and the rs1333049 G>C in the CDKN2-AS1 gene on chromosome 9 (recessive model; OR=1.228; 95% CI 1.001 – 1.518; p=0.050). The Kaplan-Meier cumulative event curves in the TCF21 variant rs12190287 G> C showed that the GC+CC vs GG genotype was associated with a worse prognosis (log-rank test, p=0.016) and the CDKN2B-AS1 rs1333049 G> C revealed that the CC vs GG+GC genotype also presented severe prognosis and more events at the end of the follow-up period (log-rank test, p=0.046). Conclusion: We have identified two SNPs associated with the prognosis of CAD, rs12190287 of TCF21 gene and rs1333049 of CDKN2-AS1 gene. Both are in non-coding enhancer regions and regulate transcriptional mechanisms shared among multiple CAD risk loci and could provide new insights into CAD's pathophysiology identifying core mechanisms for therapeutic intervention modulating the disease risk. FUNDunding Acknowledgement: Type of funding sources: None.